The Governmental Regulation No. 2 of 2020 and the Head of the Region General Election in the Pandemic ERA: Between the Health Protocol and Cluster Disaster of the Regional General Election (Medico Legal Update, 2020)
Objective: The organization of the regional general election during the Covid-19 pandemic surely createsthreats towards the citizens’ right to live, which is guaranteed by the constitution. It is not easy to guaranteethe safety of the organizers as well as the voters and to build a discipline in running the health protocolduring the regional general election This paper aims to describe such condition.Method: This research uses the juridical-normative method with the descriptive-qualitative approach.Result: There needs to be a tight and a measured health protocol which is able to prevent the turning ofthe regional general election into an arena of mass Covid-19 infection. It is important to strengthen theregulation in the form of prohibitions and sanctions in violating the protocol.Conclusion: The General Election Commission and the government must act strictly to every violationof the health protocol, as it endangers many people. There must be clear regulations on the prohibition ofthe general election campaign and activities which involve many people in the red areas, and campaignlimitations in the green areas.